Precision measurement of a brown dwarf mass in a binary system in the microlensing event - OGLE-2019-BLG-0033/MOA-2019-BLG-035 - Herald, Amey J.; Udalski, A.; Bozza, V.; Rota, P.; Bond, I. A.; Yee, J. C.; Sajadian, S.; Mróz, P.; Poleski, R.; Skowron, J.; Szymański, M. K.; Soszyński, I.; et al. (Astronomy and astrophysics, 2022)
Context. Brown dwarfs are transition objects between stars and planets that are still poorly understood, for which several competing mechanisms have been proposed to describe their formation. Mass measurements are generally difficult to carry out for isolated objects as well as for brown dwarfs orbiting low-mass stars, which are often too faint for a spectroscopic follow-up.Aims. Microlensing provides an alternative tool for the discovery and investigation of such faint systems. Here, we present an analysis of the microlensing event OGLE-2019-BLG-0033/MOA-2019-BLG-035, which is caused by a binary system composed of a brown dwarf orbiting a red dwarf.Methods. Thanks to extensive ground observations and the availability of space observations from Spitzer, it has been possible to obtain accurate estimates of all microlensing parameters, including the parallax, source radius, and orbital motion of the binary lens.Results. Following an accurate modeling process, we found that the lens is composed of a red dwarf with a mass of M1 = 0.149 ± 0.010 M⊙ and a brown dwarf with a mass of M2 = 0.0463 ± 0.0031 M⊙ at a projected separation of aub> = 0.585 au. The system has a peculiar velocity that is typical of old metal-poor populations in the thick disk. A percent-level precision in the mass measurement of brown dwarfs has been achieved only in a few microlensing events up to now, but will likely become more common in the future thanks to the Roman space telescope.
Gesehen am 07.12.2022